Phytochemical Compound, Antioxidant and Antibacterial Properties of Sargassum sp. Extracts from Pahawang Island, Lampung Province - Iffa Afiqa Khairani; Khaerunissa Anbar Istiadi; Nawang Restiawati (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Pahawang Island, located in Lampung Bay, has a variety of potential natural resources, one of which is macroalgae. One of the abundant brown macroalgae is Sargassum sp., with phytochemical components (flavonoids, steroids, tannins, and glycosides) that have potential as antioxidants, antibacterial, antitumor, anticancer, antifouling, and others. Sargassum sp. from Lampung waters, especially Pahawang Island still lacks scientific studies on its bioactive content and properties. This study aims to examine the phytochemical compounds (qualitatively and quantitatively), antioxidant activity (DPPH method) and antibacterial potential of Sargassum sp. extract (MIC/MBC method) against Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The results of phytochemical assay  showed that Sargassum sp. extract contained phenolic compounds, flavonoids, tannins, and saponins. Quantification results on total phenolic content were 0.56 mgGAE/g extract, total tannins were 4.27 mgTAE/g extract, total flavonoids were 14.19 mgQE/g extract, and total saponins were 5.54 %. Sargassum sp. extract classified as a very weak antioxidant with IC50 value of 964.10 ppm, and moderate antibacterial activity at a concentration of MIC/MBC 250/250 ppm against B. subtilis, E. coli, P. aeruginosa, and S. aureus